Conservation of the Protein Composition and Electron Microscopy Structure of Drosophila melanogaster and Human Spliceosomal Complexes - Herold, Nadine (American Society for Microbiology (ASM), 2009)
Comprehensive proteomics analyses of spliceosomal complexes are currently limited to those in humans, and thus, it is unclear to what extent the spliceosome's highly complex composition and compositional dynamics are conserved among metazoans. Here we affinity purified Drosophila melanogaster spliceosomal B and C complexes formed in Kc cell nuclear extract. Mass spectrometry revealed that their composition is highly similar to that of human B and C complexes. Nonetheless, a number of Drosophila-specific proteins were identified, suggesting that there may be novel factors contributing specifically to splicing in flies. Protein recruitment and release events during the B-to-C transition were also very similar in both organisms. Electron microscopy of Drosophila B complexes revealed a high degree of structural similarity with human B complexes, indicating that higher-order interactions are also largely conserved. A comparison of Drosophila spliceosomes formed on a short versus long intron revealed only small differences in protein composition but, nonetheless, clear structural differences under the electron microscope. Finally, the characterization of affinity-purified Drosophila mRNPs indicated that exon junction complex proteins are recruited in a splicing-dependent manner during C complex formation. These studies provide insights into the evolutionarily conserved composition and structure of the metazoan spliceosome, as well as its compositional dynamics during catalytic activation.